A Literature Review of Women's Sports in Social Dynamics: Foucault's Genealogy - Desviyanti, Elsya; Vai, Aref; Rahmatullah, Muhammad Imam (Universitas Negeri Semarang, 2023)
This review article provides an overview of the reality of sports women in the life of social dynamics. The method used is a literature study or literature review. Literature study or literature review is a research design used to collect data or sources related to a particular topic by reading, recording and managing research materials. The purpose of this method is to reveal various theories that are relevant to the problem under study. In the search conducted through the keyword